Why were innovators motivated to be entrepreneurs? An empirical study of Taiwanese start-ups - Chia-Liang Hung (Administrative Sciences, 2022)
Background: According to the lead user theory, lead users at the front of a market, benefiting significantly from new products, usually have more innovation intension than general users. However, little research depicts the entrepreneurship motivations that drive innovators to become businesspeople. Hence, this study investigates Taiwanese entrepreneurs to fill this gap in the research. Method: This study examines motivations for becoming an entrepreneur from small- and medium-sized enterprises in Taiwan. A multiple regression analysis is used to examine the relationship between lead user inclination and entrepreneurial motivations as well as to test the moderating effect of community involvement. Results: The research results summarise entrepreneurial motivations into five categories: product knowledge advantage, industry expertise, inducements to innovation, career expectations, and benchmarking and indicate the positive moderating effect of community involvement on the association between innovators and entrepreneurs. Conclusions: Additional research is suggested to catalyse motivations to aspire lead users to pursue business success as well as to enhance entrepreneurship education policy. This study contributes to understanding the inclination of lead users towards becoming entrepreneurs and, especially, to emphasise the role of community involvement, which increases the likelihood of innovators to be entrepreneurs.
Keywords: 350; entrepreneurship; lead user; motivation; user community; user entrepreneur